Maternal information-seeking on pregnancy-induced hypertension and associated factors among pregnant women, in low resource country, A cross-sectional study design. - Ayana Alebachew Muluneh; Fekade Demeke Bayou; Kegnie Shitu; Ayenew Sisay Gebeyew; Sefefe Birhanu Tizie; Mulugeta Desalegn Kasaye; Adamu Ambachew Shibabaw; Agmasie Damtew Walle (PLOS Digital Health)
Pregnancy-induced hypertension is the most prevalent medical problem associated with pregnancy. It has been reported to affect 6-10% of all pregnant women worldwide. Mothers' failure to seek information related to PIH increases the risk of death from the complication of pregnancy-induced hypertension. This study aimed to assess PIH information-seeking behaviour and its associated factors among pregnant women in rural Sekela Woreda. A community-based cross-sectional study was conducted from May 15 to June 15, 2022. An interviewer-administered structured questionnaire was used to collect the data. The sample size was 635. A cluster sampling technique was used to select the sampled kebeles. The study population included rural pregnant women. This study included pregnant women who were permanent residents of the study area, whereas this study excluded pregnant women who were admitted only for delivery services and temporary residents who visited the study area. The mean age of the participants was 31.8 ± 6.09 years, with minimum and maximum ages of 20 and 45 years, respectively. We conducted descriptive analysis, bivariable analysis, and multivariable analysis to identify determinants of PIH information seeking. The proportion of pregnancy-induced hypertension (PIH) information seeking among pregnant women was 214 (35.4%) out of 604. Pregnant mothers aged 35 years and above (AOR =0.67, 95% CI =0.46, 0.97), family resistance (AOR = 0.45, 95% CI =0.29, 0.69), health care satisfaction (AOR =1.7, 95% CI =1.1, 2.5), and perceived severity of pregnancy-induced hypertension (PIH) (AOR =1.6, 95% CI =1.1, 2.4) were significantly associated with pregnancy-induced hypertension information seeking. According to our findings Information seeking related to pregnancy-induced hypertension is low. Aged mothers, family resistance, mothers' satisfaction with health care services, and perceived severity of PIH were found to be associated with pregnancy-induced hypertension information seeking. Expanding health education programs for pregnant women and providing awareness and training about PIH to participants and their husbands is the most effective way to reduce the prevalence of PIH complications.